2002
DOI: 10.1002/jnr.10411
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor treatment promotes mobilization of young but not aged adult subventricular zone precursors in response to demyelination

Abstract: Precursor cells of the adult mouse subventricular zone (SVZ) are mobilized and recruited by a lysolecithin (LPC)-induced demyelination of the corpus callosum. Because age decreases the proliferation of the SVZ neural precursors as well as the potential for myelin repair of the adult central nervous system, we have compared the ability of young and aged adult neural precursors to respond to LPC-induced demyelination. With age, the SVZ cells lost their capacity to proliferate and to be recruited by the lesion. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…Furthermore, MS lesions, especially those in the periventricular white matter, show evidence of progenitor cell activation in the SVZ and mobilization to lesion areas [44]. Thus, growth factors that promote recruitment of OP cells to lesions from the SVZ may enhance the repair response from endogenous cell populations, as has been reported from animal studies [5,42]. Proliferation of SVZ cells in the adult CNS can be stimulated by FGF2 and/or EGF [45,46].…”
Section: Tapping Into Multiple Sources Of Op Cellsmentioning
confidence: 84%
See 3 more Smart Citations
“…Furthermore, MS lesions, especially those in the periventricular white matter, show evidence of progenitor cell activation in the SVZ and mobilization to lesion areas [44]. Thus, growth factors that promote recruitment of OP cells to lesions from the SVZ may enhance the repair response from endogenous cell populations, as has been reported from animal studies [5,42]. Proliferation of SVZ cells in the adult CNS can be stimulated by FGF2 and/or EGF [45,46].…”
Section: Tapping Into Multiple Sources Of Op Cellsmentioning
confidence: 84%
“…However, analysis of remyelination can be complicated in EAE models because modulation of the growth factor or cytokine under study can also alter the immune response and disease severity [3,4]. Gliotoxin models, such as injection of lysolecithin or ethidium bromide or ingestion of cuprizone, can accomplish a relatively specific period of demyelination after which the demyelinating agent is no longer active [5][6][7]. Therefore, gliotoxin models circumvent the autoimmune complexity and provide a reproducible demyelination episode to simplify analysis of cellular responses associated with remyelination.…”
Section: Necessity For Different Models Of Experimental Demyelinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Tsiperson et al (2015) also demonstrated that following demyelination by cuprizone, an increase in PDGFR␣ progenitors was observed in wild mice as a result of increased DNA synthesis and cell proliferation. According to Decker et al (2002), cytokines and growth factors released either from widespread inflammatory and glial cells (Levine, 1994) or from damaged axons after demyelination (Di Bello et al, 1999), induce OPCs to reenter the cell cycle after demyelination.…”
Section: Discussionmentioning
confidence: 99%